PENGARUH PROGRAM PELATIHAN DAN PENGEMBANGAN KARIR PEGAWAI TERHADAP KUALITAS LAYANAN - Arka'a Ahmad Agin (JEM Jurnal Ekonomi dan Manajemen, 2017)
Purpose of this study is to analyze the effect of employee training programs, career development on service quality PT Bumi Bangka Belitung Sejahtera. The population in this research are employees of PT Bumi Bangka Belitung Sejahtera who have attended training or development program or both. The results showed that simultaneously employee training and career development have a significant effect on service quality. While the partial training of employees has no significant effect on service quality. While career development has a significant effect on service quality. Career development variable has a dominant influence on service quality at PT Bumi Bangka Belitung Sejahtera